Translation techniques of the positive politeness utterances in the Pay It Forward movie - Widiaswara, R. Anantama; Jumanto, Jumanto (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2024)
This descriptive qualitative research employed the methods of observation and auto-expert judgment for the data collection and applied Brown & Levinson’s politeness theory (1987) and Molina & Albir’s translation theory (2002) for the data analysis. This research focused on finding the positive politeness strategies and the translation techniques of the utterances obtained from Pay It Forward movie as the data source. Based on the findings of the research, there were 40 utterances with positive politeness strategies as the data under analysis. The research findings, among others, showed that the strategies of Intensify interest to hearer (17.50%) and Exaggerate (17.50%) were dominantly used in the Pay It Forward movie, while the translation strategy of Established equivalent (40.00%) was mostly used in the translation of positive politeness utterances in the movie. It can be concluded here that the translator translates the positive politeness utterances of the source language (English) into the target language (Indonesian) appropriately through the Established equivalent strategy without making any significant changes to maintain the meaning relatively the same in the Indonesian translation subtitles.